Implementasi Nilai-Nilai Bela Negara Pada Penggunaan Tenaga Kerja Asing Ditinjau Dari Perspektif Undang - Undang Cipta Kerja - Aslihatin Zuliana; Irwan Triadi (LPPM Universitas Sains dan Teknologi Komputer, 2024)
Foreign workers employed in Indonesia are intended to meet the needs of the national labor market by filling gaps in skills and competencies in certain fields that are not covered by Indonesian workers. There are limitations on the use of foreign workers in Indonesia, which are regulated by Law No. 6 of 2023 on the Determination of Government Regulation in Lieu of Law No. 2 of 2022 on Job Creation as Law, which aims to ensure that the presence of foreign workers in Indonesia is not seen as a threat to Indonesian workers. Previously, regulations related to the use of foreign workers were accommodated through Law No. 13 of 2003 on Manpower, the change from the old regulation to the new regulation has loopholes that could potentially lead to violations of the use of TKA. In the face of this condition, it is necessary to review the applicable regulations related to administrative sanctions for foreign workers and foreign worker employers in order to protect the rights of Indonesian workers can be achieved as an embodiment of Defense in the field of Manpower.